Evaluation of sanitary status of grapevines in the Czech Republic - P. Komínek; V. Holleinová (Plant, Soil and Environment, 2003)
A survey was made to evaluate sanitary status of grapevines in the Czech Republic with regard to occurrence of economically important viruses. Propagation material of 109 grapevine clones was tested for presence of Grapevine fanleaf virus, Arabis mosaic virus, Grapevine leafroll-associated virus 1, Grapevine leafroll-associated virus 3, Grapevine virus A, Grapevine virus B and Grapevine fleck virus. Dormant canes were collected and cortical scrappings were analyzed by DAS-ELISA. All seven viruses tested were found to be widely spread in Czech propagation material of grapevine. From 330 individual vines tested, 148 vines were found to be infected with at least one virus. From 109 clones tested, in 98 clones at least one vine negative for tested pathogens was found. Such vines were promoted as candidate plants into screenhouse in Faculty of Horticulture Lednice and will be further tested by other methods. Sanitation of infected grapevine clones is needed in near future.